Anti‐PF4 testing for vaccine‐induced immune thrombocytopenia and thrombosis (VITT): Results from a NEQAS, ECAT and SSC collaborative exercise in 385 centers worldwide. (6th June 2022) - Reilly‐Stitt, Christopher; Jennings, Ian; Kitchen, Steve; Makris, Mike; Meijer, Piet; de Maat, Moniek; Scully, Marie; Bakchoul, Tamam; Walker, Isobel D.
Abstract: Background: Vaccine‐induced immune thrombocytopenia and thrombosis (VITT) following the administration of the AstraZeneca (AZ) ChAdOx1 nCOV‐19 vaccine is a well recognized clinical phenomenon. The associated clinical and laboratory features have included thrombosis at unusual sites, thrombocytopenia, raised D‐dimer levels and positivity for immunoglobulin G (IgG) anti‐platelet factor 4 (PF4) antibodies. Objectives: A collaborative external quality assessment (EQA) exercise was carried out by distributing five lyophilized samples from subjects with VITT and one from a healthy subject to 500 centers performing heparin‐induced thrombocytopenia (HIT) testing. Methods: Participating centers employed their locally validated testing methods for HIT assays, with some participants additionally reporting results for VITT modified assays. Results: A total of 385 centers returned results for anti‐PF4 immunoassay and functional assays. The ELISA assays used in the detection of anti‐PF4 antibodies for the samples distributed had superior sensitivities compared with both the functional assays and the non‐ELISA methods. Conclusion: ELISA‐based methods to detect anti PF4 antibodies have a greater sensitivity in confirmation of VITT compared with functional assays regardless of whether such functional assays were modified to be specific for VITT. Rapid immunoassays should not be employed to detect VITT antibodies.